Implementation of interventions designed to promote healthy sleep and circadian rhythms in shiftworkers. (3rd April 2021) - Harrison, Elizabeth M.; Schmied, Emily A.; Yablonsky, Abigail M.; Glickman, Gena L.
ABSTRACT: Shiftwork is a significant risk factor for a host of negative health and safety outcomes, which have been at least partly attributed to disturbances of the circadian timing system. As a result, an entire sub-field of chronobiology has been devoted to developing and evaluating countermeasures for circadian misalignment, sleep disruption, fatigue, and other issues associated with shiftwork. Much of this research takes place under highly controlled laboratory conditions due to the necessity of accurately characterizing individual rhythms, both for intervention design and assessment of efficacy. Applied studies of interventions for shiftworkers are, by their nature, more complicated, often demonstrating less consistent findings. While this, in part, reflects execution under less rigorously controlled conditions, it may also stem from variability in implementation approaches. A systematic review of published studies (through May 2017) of interventions designed to enhance circadian health in shiftworkers was conducted to determine the frequency and quality of the assessment of implementation as well as barriers and enablers to implementation. A search of PubMed, PsychINFO, Web of Science, and CINAHL databases yielded a total of 5368 unique references. After a title and abstract screen, 323 proceeded to full-text review; 68 of those met final criteria for data extraction. Implementation was assessed to some degree in 60.3% of those 68 articles. Where it was assessed, the mean quality score on a scale from 1 to 5 (1 = very little, 3 = moderate, 5 = very in-depth) was 2.56. One or more enablers were identified in just 17 of the 68 studies (25.0%), and barriers in just 18 (26.5%). Implementation of these interventions is a critical but seldom-acknowledged component of their uptake and effectiveness, and we highly recommend that future shiftworker intervention research make an effort to incorporate formalized assessments of implementation and/or hybrid effectiveness-implementation approaches.